Optimizing optical, dielectric, and electrical properties of polyvinyl alcohol/polyvinyl pyrrolidone/poly(3,4-ethylene dioxythiophene) polystyrene sulfonate/NiO-based polymeric nanocomposites for optoelectronic applications - E. Salim; A. Magdy; A. H. EL-Farrash; A. El-Shaer (Scientific Reports)
Abstract An electro- and optically favorable quaternary nanocomposite film was produced by solution-casting nickel oxide nanoparticles (NiO NPs) into polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), and poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT/PSS). Based on transmission electron microscopy (TEM) and X-ray diffraction (XRD) observations, the synthesized NiO NPs have a cubic phase and a diameter between 10 and 45 nm. The complexity and interactions observed through XRD patterns, UV–visible spectra, and FTIR measurements suggest that the NPs are not just dispersed within the polymer matrix, but are interacting with it, leading to enhanced dielectric properties and AC electrical conductivity. From 9 × 103 to 3.22 × 103 Ω, NiO NPs concentrations reduce bulk resistance Rb, indicating more linked conductive channels. The dielectric tests showed that polarized nanoparticles increased polarizability under electric field conditions. The incorporation of NiO NPs boosted DC conductivity from 1.25 × 10–6 to 5.64 × 10–5 S m−1. The mobility of NiO NPs boosts DC conductivity linearly with field frequency. These interactions can lead to improved electrical conductivity, energy storage capabilities, and overall efficiency of the nanocomposite, making it a promising material for various applications.